Biosecurity (Taylor & Francis, 2024)
Biosecurity: A Systems Perspective provides an overview of biosecurity as a system of related components, actors, and risks. This book—directed to the biosecurity practitioner, generalist scientist, and student—introduces overall features of the biosecurity system while walking the reader through the most up-to-date research on each step of the continuum (i.e. pre-border, border, and post-border activities). This book, which explicitly incorporates economic and social dimensions as well as varied decision-making contexts, paves the way for a more systemic approach to biosecurity risk management. The work spans statistics, ecology, mathematics, economics, veterinary science, human medicine, and sociology, involving collaborators across government, academia, and the private sector.